Simulating labor supply behavior when workers have preferences for job opportunities and face nonlinear budget constraints - John K. Dagsvik; Marilena Locatelli; Steinar Strøm (University of Oslo, Department of Economics, 2006)
This paper analyzes the properties of a particular sectoral labor supply model developed and estimated in Dagsvik and Strøm (2006). In this model, agents have preferences over sectors and latent job attributes. Moreover, the model allows for a representation of the individual choice sets of feasible jobs in the economy. The properties of the model are explored by calculating elasticities and through simulations of the effects of particular tax reforms. The overall wage elasticities are rather small, but these small elasticities shadow for much stronger sectoral responses. An overall wage increase and, of course, a wage increase in the private sector only, gives women an incentive to shift their labor supply from the public to the private sector. Marginal tax rates were cut considerably in the 1992 tax reform. We find that the impact on overall labor supply is rather modest, but again these modest changes shadow for stronger sectoral changes. The tax reform stimulated the women to shift their labor from the public to the private sector and to work longer hours. A calculation of mean compensated variation shows that the richest households benefited far more from the 1992 tax reform than did the poorest households.
Keywords: C51; J22; 330; Labor supply; married females; structural model; sectoral choice; wage elasticities; evaluation of tax reforms; Arbeitsangebot; Frauenerwerbstätigkeit; Wirkungsanalyse; Simulation; Norwegen